A the analysis wholesale market telecommunications in Republic Serbia - Rudež Jovan; Gajić Aleksandar; Vujičić Slađana (Trendovi u Poslovanju, 2019)
Each organization has specific goals, purchasing policies and procedures, organizational structures and systems. In general, business buyers strive to maximize the benefits (economic, technical, service, and social) of the costs of market supply. The incentive for a business buyer to buy will be a relatively higher proportion of the perceived benefit and cost. The business market consists of all organizations that procure goods and services that they use in the production of other goods and services which they then sell, rent or supply to others. More money and more items are included in sales to business customers than in sales to consumers.